The study of the image in tourism. An approach to its main definitions - Sanchez Castellanos, Sandra Milena (2022)
A documentary analysis is presented of academic articles that address the subject of image in tourism, definition, characteristics and integrating elements of the concept; typology in tourism and its relationship with image; countries that develop research on the subject and its influence on the development of tourism activity. Considering the importance of image in the information process, 70 studies published in research journals, found in the Dialnet, EBSCO, Redalyc and Scielo databases, were compiled for a period of time from 2005 to 2020. The research technique and instrument is the document review matrix, created to analyze: document identification factors, document citation factors, document location and impact factors and document theoretical analysis factors. In a context of virtuality and rapid access to technology, rather than completely replacing the definition that dates back to 1972, what is observed is that the image in tourism has coupled elements of each new tourism dynamic and market trends.